The financial innovation hypothesis: Schumpeter, Minsky and the sub-prime mortgage crisis - Eugenio Caverzasi; Daniele Tori (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
Neo-Schumpeterian economics inspired by the work of Schumpeter and the financial Keynesianism of Minsky are often regarded as unrelated theoretical strands. In this paper, we try to combine these two literatures building on a parallelism between non-financial and financial firms. We focus on recent financial innovations, highlighting how the evolution experienced by US financial institutions led them to transcend their traditional role of credit providers, shaping as "producers" of financial products, through securitization. This allows on the one hand to broaden the application of Neo-Schumpeterian insights to the financial sector and, on the other, to provide an original explanation of the so-called sub-prime crisis by applying the Financial Instability Hypothesis of Minsky to the alternative context of financial production. We maintain that the 2007-8 crisis was not the result of an innovation in the real sector, but came from an innovation (or a series of innovations) intrinsic to the financial system itself, which fostered credit creation. We argue that this "cluster of innovations" can be placed under the label "securitization", defined as the business of packaging and reselling loans, with repo agreements as the main source of funds.
Keywords: B52; G21; O33; 330; Minsky; Schumpeter; securitization; financial firms; Great Financial Crisis